2018
DOI: 10.1007/s40801-018-0143-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Definitive Drug–Drug Interaction Testing on Medication Management and Patient Care

Abstract: Background and ObjectiveAegis Sciences Corporation developed a test (InterACT Rx™) that objectively and definitively identifies substances known to interact with drug–drug interaction-prone medications commonly prescribed in the treatment of chronic pain and behavioral health disorders. The objective of this study was to assess the severity of identified drug–drug interactions, the reduction in the frequency and severity of identified drug–drug interactions, and the impact of the test on healthcare utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Many hospital admissions of older adults for drug toxicity occur after administration of a drug known to cause DDIs [ 34 ]. Although continuous monitoring for DDIs and adjustment of medications require diligence on the part of treating clinicians to ensure patient safety, studies have shown that evaluating polypharmacy and DDIs and updating treatment plans accordingly is associated with decreased healthcare and medication costs [ 35 , 36 ]. Furthermore, deprescribing of medications should be considered for patients with OAB who are receiving polypharmacy; in such cases, it may be necessary for providers to carefully consider baseline medication use, prioritize medications, and discontinue or change medications (e.g., from anticholinergics for OAB to adrenergic agonists) to optimize clinical outcomes [ 27 ].…”
Section: Healthcare Burden Of Polypharmacymentioning
confidence: 99%
“…Many hospital admissions of older adults for drug toxicity occur after administration of a drug known to cause DDIs [ 34 ]. Although continuous monitoring for DDIs and adjustment of medications require diligence on the part of treating clinicians to ensure patient safety, studies have shown that evaluating polypharmacy and DDIs and updating treatment plans accordingly is associated with decreased healthcare and medication costs [ 35 , 36 ]. Furthermore, deprescribing of medications should be considered for patients with OAB who are receiving polypharmacy; in such cases, it may be necessary for providers to carefully consider baseline medication use, prioritize medications, and discontinue or change medications (e.g., from anticholinergics for OAB to adrenergic agonists) to optimize clinical outcomes [ 27 ].…”
Section: Healthcare Burden Of Polypharmacymentioning
confidence: 99%
“…7,8 Similarly, DDIs are known to contribute to adverse drug events, 9,10 and strategies to manage DDIs have been shown to improve patient outcomes. 11 Given their important clinical implications, recommendations to manage DDIs are included both in FDA drug development guidance to industry 12 and in numerous clinical practice guidelines. 13,14…”
Section: Introductionmentioning
confidence: 99%
“…Drug–drug interactions (DDIs) are underdiagnosed, accounting for more than 30% of all adverse drug events (ADEs) [ 1 , 2 , 3 ], which cost the collective healthcare system an estimated USD 30.1 billion [ 4 , 5 , 6 , 7 ]. The number of patients taking five or more prescription drugs has more than doubled between 1988 and 2018 [ 8 ], while past research confirms that the risk of an ADE or DDI increases with polypharmacy [ 9 ], highlighting the urgent need for a DDI test with demonstrable clinical utility.…”
Section: Introductionmentioning
confidence: 99%